Mental health, eating disorder risk, and disordered eating patterns among Lebanese National Taekwondo Players: A cross-sectional study - Maha Hoteit; Hassan Karaki; Amal Haidar; Rana Baroud; Habib Zarifeh; Ayoub Saidi; Fadi Kibbeh; Nathalie Jbeily; Zahra Sadek (PLoS ONE, 2025)
Objectives Elite athletes, particularly those engaged in combat sports like Taekwondo, are exposed to unique physical and psychological stressors. These demands may increase vulnerability to mental health challenges such as anxiety and depression, as well as disordered eating behaviors, especially when weight categories and performance pressures are involved. This study aimed to establish the mental health profile of Lebanese Taekwondo players while exploring the potential relationship between the psychological health indicators and eating disorders or disordered eating patterns. Methods This cross-sectional study was conducted from January to July 2023 on 110 Lebanese black belt Taekwondo players recruited through the Lebanese Taekwondo Federation. Data collection involved anthropometric measurements, body composition analysis, and a self-administered questionnaire covering sociodemographic and socioeconomic factors, health behaviors, the Sport Mental Health Assessment Tool-1 (SMHAT-1) and the Eating Attitudes Test-26 (EAT-26). Results This study involved 110 Lebanese Taekwondo players (mean age 24.28 ± 10.5 years, 67.3% male), with the majority under 24 years old and half unemployed. Participants reported various socioeconomic challenges, including income reductions due to the post-economic crisis. Mental health assessments using the SMHAT-1 questionnaire revealed 14.5% were at high risk for anxiety, with female athletes exhibiting significantly higher anxiety scores (p = 0.006). Depression was reported in 13.6% of athletes, particularly among females (30% vs 5%, p = 0.000), and 10% had self-harm thoughts. Sleep disturbances affected 24.5% of participants, while 12.7% reported alcohol misuse. Disordered eating (DE) patterns were more common in females (50%) compared to males (p = 0.01), and the overall prevalence of DE was 33.6%. Using the EAT-26 questionnaire, 15.5% of participants were at risk of eating disorders (ED), with no significant gender differences. Factors such as unemployment, high exercise volume (≥10 hours per week), and reduced income were associated with higher ED risk. Depression and Psychosis were linked to both ED and DE, while anxiety was only associated with DE. Binary logistic models showed that athletes facing salary reductions were affected by ED, while those with psychosis had an 11-fold increased risk for ED. Household income and ADHD were strongly associated with DE patterns. Conclusion This study revealed significant connections between mental health indicators and eating disorders or disordered eating patterns among Lebanese Taekwondo players. The findings highlight the need for targeted interventions, increased mental health awareness, and the development of prospective programs tailored to enhance athletes’ well-being and performance, including personalized mental health support.